PELATIHAN DAN PENGAKUAN PROFESIONAL SEBAGAI DETERMINAN PILIHAN KARIR SEBAGAI AKUNTAN PENDIDIK - Harahap, Ludwina; Efendri, Efendri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The study aims to test the influence of professional recognition and training on the interest in becoming an educator accountant for Accounting students in South Jakarta. This study used the structural equation modeling (SEM) method from 100 students as a sample selected by purposive sampling technique. The results show that these two factors significantly influenced students' interest in becoming educator accountants. For future study, suggested adding other factors that may influence career choices as an educator accountant, such as economic motives, family support, or other factors. The implications of this research are helping students in choosing a career, especially accounting students. Another implication is suggesting to educational institutions equip the student with ts some professional training to support student career selection. This research may add to the study of student career choices